Surface Chemistry Mechanism of Ultra-Low Interfacial Resistance in the Solid-State Electrolyte Li7La3Zr2O12 - Sharafi, Asma; Kazyak, Eric; Davis, Andrew L; Yu, Seungho; Thompson, Travis; Siegel, Donald J; Dasgupta, Neil P; Sakamoto, Jeff (Chemistry of materials, 2017)
The impact of surface chemistry on the interfacial resistance between the Li7La3Zr2O12 (LLZO) solid-state electrolyte and a metallic Li electrode is revealed. Control of surface chemistry allows the interfacial resistance to be reduced to 2 Ω cm2, lower than that of liquid electrolytes, without the need for interlayer coatings. A mechanistic understanding of the origins of ultra-low resistance is provided by quantitatively evaluating the linkages between interfacial chemistry, Li wettability, and electrochemical phenomena. A combination of Li contact angle measurements, X-ray photoelectron spectroscopy (XPS), first-principles calculations, and impedance spectroscopy demonstrates that the presence of common LLZO surface contaminants, Li2CO3 and LiOH, result in poor wettability by Li and high interfacial resistance. On the basis of this mechanism, a simple procedure for removing these surface layers is demonstrated, which results in a dramatic increase in Li wetting and the elimination of nearly all interfacial resistance. The low interfacial resistance is maintained over one-hundred cycles and suggests a straightforward pathway to achieving high energy and power density solid-state batteries.